Differential relationships between autistic traits and anthropomorphic tendencies in adults and early adolescents - Gao, Rui-Rui; Si, Shang-Wen; Lin, Xiao-Xiao; Wang, Yu-Zheng; Wang, Ning; Wang, Jin-Yan; Luo, Fei (Frontiers in Psychology, 2024)
Anthropomorphism, the attribution of human-like qualities (e.g., mental states) to nonhuman entities, is a universal but variable psychological experience. Adults with professionally diagnosed autism or high levels of subclinical autistic traits consistently show greater tendencies to anthropomorphize, which is hypothesized to reflect 1) a compensatory mechanism for lacking social connections and 2) a persistence of childhood anthropomorphism into adulthood. Here we directly tested these hypotheses in a general population sample consists of both adults (N=685, 17–58 years old) and early adolescents (N=145, 12–14 years old) using the refined 9-item Anthropomorphism Questionnaire (AnthQ9; Clutterbuck et al., 2022), which measures both present and childhood anthropomorphic tendencies. We found that loneliness partially mediated autistic traits and presentational anthropomorphism in adult sample, adults with heightened autistic traits reported increased present anthropomorphism (e.g., tend more to perceive computers as having minds), but which hold even after controlling for social connectedness. In contrast, adolescents with heightened autistic traits did not show increased present anthropomorphism, but rather reported reduced childhood anthropomorphism (e.g., tend less to perceive toys as having minds) after controlling for social connectedness. We also found evidence that the present and childhood subscales of the AnthQ9 might tap into essentially different aspects of anthropomorphism. The results suggest that increased anthropomorphic tendencies in adults with heightened autistic traits cannot be explained solely by increased sociality motivation, but may be due to delayed development of anthropomorphism, although alternative possibilities of measurement problems cannot be ruled out. Implications for the measurement of anthropomorphism and its relation with theory of mind were also discussed.